Nrf2 and HSF-1 Pathway Activation via Hydroquinone-Based Proelectrophilic Small Molecules Is Regulated by Electrochemical Oxidation Potential. (31st July 2015) - Satoh, Takumi; Stalder, Romain; McKercher, Scott R.; Williamson, Robert E.; Roth, Gregory P.; Lipton, Stuart A.
Activation of the Kelch-like ECH-associated protein 1/nuclear factor (erythroid-derived 2)-like 2 and heat-shock protein 90/heat-shock factor-1 signal-transduction pathways plays a central role in combatting cellular oxidative damage and related endoplasmic reticulum stress. Electrophilic compounds have been shown to be activators of these transcription-mediated responses through S -alkylation of specific regulatory proteins. Previously, we reported that a prototype compound (D1, a small molecule representing a proelectrophilic, para -hydroquinone species) exhibited neuroprotective action by activating both of these pathways. We hypothesized that the para -hydroquinone moiety was critical for this activation because it enhanced transcription of these neuroprotective pathways to a greater degree than that of the corresponding ortho -hydroquinone isomer. This notion was based on the differential oxidation potentials of the isomers for the transformation of the hydroquinone to the active, electrophilic quinone species. Here, to further test this hypothesis, we synthesized a pair of para - and ortho -hydroquinone-based proelectrophilic compounds and measured their redox potentials using analytical cyclic voltammetry. The redox potential was then compared with functional biological activity, and the para -hydroquinones demonstrated a superior neuroprotective profile.